1970
DOI: 10.3329/jbau.v6i2.4828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citric acid and acetic acid on the performance of broilers

Abstract: An experiment was conducted with commercial broilers to investigate the effects of feeding citric acid, acetic acid and their combination on their performance and to determine the economic competence of using citric acid and acetic acid in broiler rations. A total number of 108 one day old straight run broiler chicks were distributed to four dietary treatments i.e. 0 % citric or acetic acid (A) , 0.5% citric acid (B), 0.5% acetic acid (C) and their combinations 0.5% citric acid and 0.5% acetic acid (D). The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
36
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 11 publications
14
36
1
4
Order By: Relevance
“…They concluded that the increase in spleen weight with supplemental vitamin E was likely to represent an increase in the number of lymphocytes. Results of CA in the present study are justified by Islam et al (2008) who reported positive effect of citric acid on liver weight in broilers. Also, Ali et al (2012) found that dietary organic acids significantly increased the weight of liver and gizzard in Japanese quails.…”
Section: Carcass Traitssupporting
confidence: 51%
“…They concluded that the increase in spleen weight with supplemental vitamin E was likely to represent an increase in the number of lymphocytes. Results of CA in the present study are justified by Islam et al (2008) who reported positive effect of citric acid on liver weight in broilers. Also, Ali et al (2012) found that dietary organic acids significantly increased the weight of liver and gizzard in Japanese quails.…”
Section: Carcass Traitssupporting
confidence: 51%
“…However, Abdel-Fattah et al (2008) showed that the addition of 1.5 or 3% citric acid increased the Ca and P concentrations in the blood serum. However, citric acid did not affect the osteocalcin, or the blood serum content of 1,25 (OH) 2, vitamin (D) or Ca of chickens fed a diet containing 0, 0.25, 0.75 and 1.25% citric acid (Islam et al, 2010). In addition, citric acid affected mineral utilization, but did not affect the plasma mineral contents (Nourmohammadi et al, 2010).…”
Section: Egg Shape Index and Quality Of Eggshellmentioning
confidence: 86%
“…However, CA did not affect the osteocalcin, or the blood serum content of 1,25 (OH) 2 , vit. D or Ca of chickens fed a diet containing 0, 0.25, 0.75 and 1.25% CA (Islam et al, 2010). In addition, CA affected mineral utilization, but did not affect the plasma mineral contents (Nourmohammadi et al, 2010).…”
Section: Hemato-biochemical Parametersmentioning
confidence: 94%